Dampak tadarus dan tadabbur al-Qur’an terhadap kinerja karyawan Perpustakaan UIN Imam Bonjol Padang - Zulfitri, Zulfitri (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2024)
This research discusses the activities of tadarus (recitation) and tadabbur (reflection) of the Qur'an carried out by the employees of the Library of UIN Imam Bonjol Padang, which have been conducted for one year to fulfill the employees' knowledge and understanding in the field of religion. The purpose of this research is to review how these tadarus and tadabbur activities impact the performance of the employees. The method used is qualitative research (field qualitative research) that aims to describe the implementation of tadarus and tadabbur of the Qur'an at the Library of UIN Imam Bonjol Padang by examining its impact on employee performance. The research results show that the tradition of tadarus and tadabbur of the Qur'an has a positive impact on the librarians, where the majority of librarians acknowledge that these activities positively affect their work motivation, increase their faith, obedience, and knowledge, enhance inner peace and moral values, foster mutual respect, and improve teamwork. Additionally, the verses reflected upon also provide solutions to their problems, help them avoid stress and work pressure, and assist in overcoming daily challenges and obstacles.